Comparison of Transparency Index Between Regency and City in South Sumatra and Lampung Province - Sunardi Sunardi; Nur May Lena; Jovan Febriantoko (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2020)
This study aimed to determine and analyze the comparison of transparency index of each region in South Sumatra and Lampung Province. The type of the study was comparative and descriptive. Data which were used were secondary data in the form of Performance Evaluation of Local Government Implementation. Total population in this study was 32 Regencies / Cities in South Sumatra and Lampung Province. The sampling technique was purposive sampling, 3 regencies and cities did not provide complete data. The method of data collection in this study was document analysis. Data analysis techniques which were used were quantitative and qualitative analysis using independent samples t test. The results showed that the transparency index of South Sumatra Province was higher than Lampung Province. Other results also showed that the transparency index of regions with city status was lower than regions with regency status.